Ibn Abbas’s Jurisprudential Views on Illegitimate Relations- A Comparative Study- - Hamid , Jassim (Islamic Sciences Journal, 2023)
ABSTRACT The research Dealt with the Opinions of the Great companion Abdullah bin Abbas in unlawful relations, four of which are : the non-acceptance of the husband’s testimony of his wife for adultery, and the punishment for sodomy is killing , not married and married, and it is not proven with the charge, any person who makes a Sextual relation with a married woman should be killed. the punishment of a virgin who commit adultery is one hundred flogging and estrangement for a year.the adulteres who has a wife shoud be punished either with flogging or with stoning . all of the scientists depended on Ibn Abbass saying about illegitimate relations. most of his saying are well and correct.